Exploring Female Identity Construction in the White Paper on Women's Progress in China - Yang, Linxiu; Han, Yisha (Top Linguistic and Language Journal (TLLJ), 2023)
This paper explores the construction of female identity in the white paper on women's progress in China, which was released by the Chinese government in 2019 to celebrate the 70th anniversary of the founding of new China. The paper adopts transitivity system in SFL as its theoretical framework and presents both qualitative and quantitative analyses. The study reveals three female images constructed in the document: beneficiary of national attitudes and policies, contributor for the development of country, and defender of their own rights. The research on female identity construction has been explored from various perspectives, including research of female identity and research on the construction of female identity. The former concerns family identity and social identity, while the latter generally focuses on social media and literary works. In family dramas, people are concerned about the independence and integrity of female characters, which reflects the continuous awakening and development of female consciousness. In society, women are trying to achieve the value of their lives by various professions. To strengthen female's professional competitiveness and social identity, gender consciousness education is necessary. In literary works, female images constructed by male authors lack objective and plain cognitive perspective, and their works don’t portray female identity from women’s deep psychological desires. Women's self-consciousness is also lacking in their works. Female literature is crucial in Chinese modern literature, as it can help enlighten women's consciousness and establish their subjectivity. This paper provides a comprehensive analysis of the construction of female identity in the white paper on women's progress in China, which sheds light on the Chinese government's recognition and attitude towards women's cause and development. The study contributes to the research on female identity construction from the perspective of national-level policy documents, which has been largely overlooked in previous research. The findings of this study have implications for promoting gender equality and enhancing women's status and rights.